Pengaruh Binder Akrilik terhadap Sifat Fisik dan Mekanik Mortar Polimer - Sitanggang, Ronal Rius; Ismeddiyanto; Edy Saputra (Departemen Teknik Sipil, Fakultas Teknik Universitas Riau, 2023)
Initial damage to the structure occurs in the outer layers of the affected surface exposure to the peat environment and the static and dynamic movement of the structure. To prevent structural damage, the latest technological innovations are needed in the use of mortar constituent materials to increase the strength of the mortar. Polymer mortar is a composite material formed from a mixture of fine aggregates, cement, water and polymer binders or binders with a certain level. The purpose of this study is to determine the effect of the use of acrylic binders on the physical and mechanical properties of polymer mortars and the influence of peat water on the future of the mortar. The substitution of acrylic binders with water consists of 3 substitutions, namely 20%, 30% and 40% and 0% as controls. The results of the search for acrylic binders on the mortar mixture obtained a minimum physical property value at 30% acrylic use in the 28-day test, namely. The porosity value of the mortar is 9.80%, the waterabsorption value of the mortar is 4.67% and 4.72%, and the sorptivity value of the mortar is 0.70. From the value of physical properties obtained the degree of tightness of the polymer mortar well with the use of acrylic binders in the mixture. For the mechanical properties of polymer mortar, compressive strength testing is carried out with optimum compressive strength at the use of 30% acrylic. The value of the compressive strength of the mortar is 33 Mpa.